Climate Risks, Just Transition, and Central Bank Policy for Sustainable Economic Growth - Juhro, Solikin M.; Robinson, Irman; Rahadyan, Heru; Rishanty, Arnita (Jurnal Ekonomi Indonesia, 2024)
Climate change poses major challenges to the global economy and society, requiring coordinated efforts to alleviate its impacts. Given the nature of climate change, the adoption of central bank policies offers a more holistic strategy for managing and mitigating climate risks, thereby bolstering the resilience of the financial system and the economy. This paper aims to explore the critical tasks of coping with climate risks and proposes an integrated central bank climate regulatory framework to foster sustainable economic growth, by exploring the transmission mechanisms of central bank policies to support the establishment of just transition targets. The framework delineates three essential strategies, namely: (i) data, tools, and research, (ii) regulation and supervision, and (iii) climate transition policy. This paper shows that the central bank’s climate policies to manage transition risks can navigate just transition and support the achievement of sustainable economic growth. The operationalization of these strategies extends beyond the traditional purview of centralbank activities, necessitating a collaborative and synergistic approach among regulators and industry stakeholders to guide the global economy toward sustainability.